Genetic diversity and virulence of Striga hermonthica from Kenya and Uganda on selected sorghum varieties - KATAKA ATANDA JOEL; STEVEN RUNO; ALICE MUCHUGI (Smujo International, 2018)
Joel KA, Runo S, Muchugi A. 2018. Genetic diversity and virulence study of Striga hermonthica from Kenya and Uganda on selected sorghum varieties. Nusantara Bioscience 10: 111-120. Parasitic weeds pose a severe problem in agricultural production, causing massive crop losses in many regions of the world and especially Africa. One example to be considered the most significant biological constraint to food production in sub-Saharan Africa (SSA) is Striga hermonthica, the most widespread among the Striga species in the semi-arid tropical African zones. The wide geographical distribution set conditions for genetically structured populations. The genetic variations among the weed populations allow for the quick breakdown of resistance in crops hence making control of the weed difficult. Efficient and effective control of S. hermonthica demands knowledge on inherent genetic variability within local and regional races of the weed. However, the genetic diversity and virulence of S. hermonthica ecotypes in Kenya and Uganda on selected sorghum varieties remain unknown. This study aimed at evaluating the genetic diversity among seven S. hermonthica populations from locations in Kenya and Uganda using 5 primer sets of Expressed Sequence Tags-Simple Sequence Repeats (EST-SSR). The genetic diversity was moderate as shown by the Nei’s genetic distance values. AMOVA measured low genetic differentiation among the populations. This study also investigated twelve sorghum varieties for their response to S. hermonthica infection. The result demonstrated that the varieties resistance responses to S. hermonthica varied widely. The phenotype of resistant interaction was characterized by the inability of the weeds haustoria to penetrate the sorghums root endodermis due to severe necrosis and in rare cases the parasites radicle growing away from the host root. The resistant sorghum varieties were the Asareca W2, Asareca AG3, N13 and the Wild-type which had low mean number of S. hermonthica plantlets growing on their roots, while the most susceptible varieties were Sap 027, Epurpur which had the highest mean number of S. hermonthica plantlets growing on their roots. There was a highly significant difference in the means of the number of Striga growing on the roots of sorghum varieties, Striga dry biomass and S. hermonthica length between the susceptible and resistant ones. This knowledge holds unique potentiality since resistant sorghum germplasm tested will be sourced and targeted to the seven specific geographical areas where virulence of the particular S. hermonthica populations was characterized.